Evaluation of cold storage techniques to improve mass rearing of Cleruchoides noackae from Thaumastocoris peregrinus eggs - Rodrigues, Angelo Peruffo; Tavares, Wagner de Souza; Zanuncio, José Cola; Wilcken, Carlos Frederico [UNESP]; Foerster, Luis Amilton; Barbosa, Leonardo Rodrigues (Cambridge University Press (CUP), 2023)
The egg parasitoid Cleruchoides noackae Lin & Huber, 2007 (Hymenoptera: Mymaridae) is originated from Australia and the main biological control agent of Thaumastocoris peregrinus Carpenter & Dellapé, 2006 (Hemiptera: Thaumastocoridae) on Eucalyptus L'Hér (Myrtaceae). Companies that grow Eucalyptus are in need of a mass rearing protocol to increase the number of individuals produced and improve the quality of this parasitoid. The aim of this study was to define a protocol for mass rearing C. noackae in T. peregrinus eggs, based in the evaluations of the key biological attributes of this parasitoid in the parental and F1 generations, after the cold storage of the parasitised host eggs. Two methods were tested as C. noackae rearing protocols. In the first, parasitised eggs of T. peregrinus by C. noackae were cold stored for 7 days after being left in a climatic chamber at 24 ± 2°C, 60 ± 10% RH and a photoperiod of 12:12 (light:dark) h (standard environmental conditions) for 3, 6, 9 or 12 days. In the second, T. peregrinus eggs parasitised by C. noackae were maintained in a climatic chamber under standard environmental conditions for 6 days, after which these eggs were cold-stored for 0 (control), 7, 14 or 21 days. Parasitism (%), and the development period (parasitism to adult) and female proportion (%) of C. noackae were evaluated. Based on the results (parental generation: parasitism, around 45%; F1 generation: parasitism, around 55%; development period, around 16 days; female proportion, around 60%), eggs should be stored at 5°C on the sixth day after parasitism by C. noackae and maintained at this temperature for 7 days. The cold storage of T. peregrinus eggs, after parasitism, can be included in the mass rearing protocols of the parasitoid C. noackae.
Keywords: bronze bug; egg parasitoid; Eucalyptus; forest pest; host storage; parasitoid rearing